Memory device application of wide-channel in-plane gate transistors with type-II GaAsSb-capped InAs quantum dots - Liao, Yu-An; Chao, Yi-Kai; Chang, Shu-Wei; Chang, Wen-Hao; Chyi, Jen-Inn; Lin, Shih-Yen (My University, 2013)
We demonstrate room-temperature electron charging/discharging phenomena of InAs quantum dots using wide-channel in-plane gate transistors. The device based on type-II GaAsSb-capped InAs quantum dots exhibits both the longer charging and discharging times than those of the type-I counterpart with GaAs capping layers. The slow charge relaxation of GaAsSb-capped InAs quantum dots and simple architecture of in-plane gate transistors reveal the potential of this device architecture for practical memory applications. (C) 2013 AIP Publishing LLC.